Anti-Factor H Antibody Reactivity in Young Adults Vaccinated with a Meningococcal Serogroup B Vaccine Containing Factor H Binding Protein - Kelsey Sharkey (American Society for Microbiology, 2019)
ABSTRACT Meningococcal serogroup B (MenB) vaccines contain recombinant factor H binding protein (FHbp), which can complex with complement factor H (CFH) and thereby risk eliciting anti-FH autoantibodies. While anti-FH antibodies can be present in sera of healthy persons, the antibodies are implicated in autoimmune atypical hemolytic uremic syndrome and C3 glomerulopathies. We immunized 120 students with a MenB vaccine (Bexsero). By enzyme-linked immunosorbent assay (ELISA), there were small increases in serum anti-FH levels at 3 weeks postvaccination (geometric mean optical density at 405 nm [OD405], 0.54 versus 0.51 preimmunization, P ≤ 0.003 for each schedule tested). There was a similar small increase in anti-FH antibody levels in a second historical MenB study of 20 adults with stored paired preimmunization and postimmunization sera (P = 0.007) but not in three other studies of 57 adults immunized with other meningococcal vaccines that did not contain recombinant FHbp (P = 0.17, 0.84, and 0.60, respectively). Thus, humans vaccinated with MenB-4C develop small increases in serum anti-FH antibody reactivity. Although not likely to be clinically important, the data indicate a host response to FH. In the prospective MenB study, three subjects (2.5%) developed higher anti-FH titers postimmunization. The elevated titers returned to baseline within 3 to 4 months, and none of the subjects reported adverse events during the follow-up. Although anti-FH antibodies can decrease FH function, the postimmunization sera with high anti-FH antibody levels did not impair serum FH function as measured using a hemolytic assay. Thus, while additional studies are warranted, there is no evidence that the anti-FH antibodies elicited by MenB-4C are likely to cause anti-FH-mediated autoimmune disorders. (This study has been registered at ClinicalTrials.gov under registration no. NCT02583412.) IMPORTANCE Meningococci are bacteria that cause sepsis and meningitis. Meningococcal species are subdivided into serogroups on the basis of different sugar capsules. Vaccines that target serogroup A, C, Y, and W capsules are safe and highly effective. New serogroup B (MenB) vaccines target a bacterial protein that can bind to a blood protein called complement factor H (FH). While serogroup B vaccines appear to be safe and effective, there is a theoretical risk that immunization with a bacterial protein that binds host FH might elicit anti-FH autoantibodies. Autoantibodies to FH have been detected in healthy persons but in rare cases can cause certain autoimmune diseases. We found small and/or transient increases in serum antibody to FH after MenB immunization. While no serious adverse events were reported in the subjects with elevated anti-FH titers, since onset of autoimmune disease is a rare event and may occur months or years after vaccination, additional, larger studies are warranted.